Tinjauan Hukum Justice Collaborator Dalam Tindak Pidana Korupsi - Lukmansyah, Aji (Law and Humanity, 2025)
Criminal acts are very detrimental so that they cannot be ignored, efforts and steps to eradicate criminal acts need to be taken so that the community feels safe. One of the criminal acts that still often occurs in Indonesia and can be said to be quite phenomenal is corruption. Disclosing corruption cases certainly requires considerable courage and the presence of witnesses who know and are even directly or indirectly involved in the case. Witnesses who know directly and are directly involved in the case and dare to report the incident are known as witnesses who cooperate with law enforcement, or are called "Justice Collaborators". The purpose of the study is to determine the position of Justice Collaborators in criminal acts of corruption and to determine the strength of evidence by Justice Collaborators as witnesses in criminal acts of corruption. The specifications used in this study are descriptive analytical. The type of normative legal research used in this study as the main data is secondary data. The data collection method is with literature studies and data analysis with a qualitative approach.